Serum KL-6 levels reflect the severity of interstitial lung disease caused by immune checkpoint inhibitors - Xiaoping Li; Dan Xue; Qiongying Wei; Xuexue Tan (Immunobiology, 2025)
Tumor immunotherapy, particularly immune checkpoint inhibitors (ICIs), has emerged as a powerful strategy in treating malignant tumors, exhibiting efficacy in both first-line and second-line treatments for advanced non-small cell lung cancer (NSCLC). Despite their success, ICIs can lead to adverse reactions, including interstitial lung disease (ILD), with an incidence ranging from 2.7 % to 20.0 %. The lack of clear correlations with dosage, duration, or drug efficacy, coupled with nonspecific clinical manifestations, poses challenges in timely diagnosis and effective management. This study examined the association between ICIs-related ILD and serum levels of KL-6 and inflammatory markers in NSCLC patients. A total of 382 NSCLC patients with squamous cell carcinoma (SQC, n = 81), adenocarcinoma (ACA, n = 132), and large cell carcinoma (LCC, n = 169) were included, of whom 191 developed ILD following ICIs treatment. Serum KL-6, TNF-α, IL-8, and IL-6 were quantified using ELISA. Results showed significantly elevated serum KL-6 levels in ILD patients (759.35 ± 214.14 U/mL) compared to those without ILD (270.81 ± 124.98 U/mL). Cancer subtype analysis revealed increased KL-6 levels across SQC, ACA, and LCC ILD patients (SQC: 645.89 ± 255.07, ACA: 797.39 ± 192.30, LCC: 783.57 ± 191.21; p < 0.001). ROC analysis identified diagnostic thresholds for KL-6: 277.4 U/mL for SQC (sensitivity 0.9756, specificity 0.8250), 346.9 U/mL for ACA (sensitivity 0.9583, specificity 0.8333), and 281.3 U/mL for LCC (sensitivity 0.9873, specificity 0.6111). Correlation analysis showed a significant relationship between KL-6 and TNF-α (r = 0.4626, p = 0.0023), IL-8 (r = 0.5584, p = 0.0001), and IL-6 (r = 0.5336, p = 0.0003) in SQC ILD patients. These findings suggest that elevated KL-6 levels and inflammatory markers are indicative of ILD in ICIs-treated NSCLC patients, with potential diagnostic implications across cancer subtypes.